Zugänglichkeit und Adressatenorientierung von Gesetzgebung und Verwaltung: Konferenzband des Netzwerks Bessere Rechtsetzung und Bürokratieabbau - Boockmann, Bernhard; Braun, Heidrun, M.A.; Tonn, Hannah, M.A. (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Good legislation and good administrative action are of great importance for the social acceptance of politics and administration. Unfortunately, however, they are often unclear, bureaucratic and poorly tailored to the needs of citizens. How can the accessibility and addressability of administration and legislation be improved? This conference volume addresses the current situation in and potential solutions to this issue, including training, service design, digitisation and AI. The editors run the Network for Better Regulation and Bureaucracy Reduction, which continuously dedicates itself to these concerns. With contributions byBernhard Boockmann | Heidrun Braun | Mateusz Dolata | Michael Eder | Tabea Hein | Daniel Rölle | Christian Schachtner | Birgit Schenk | Christoph Schmidt | Christiane Schwabe | Gerhard Schwabe | Antje G. I. Tölle | Hannah Tonn